Disturbance observer-based adaptive fault-tolerant control for a quadrotor helicopter subject to parametric uncertainties and external disturbances - Wang, Ban; Yu, Xiang; Mu, Lingxia; Zhang, Youmin (Mechanical systems and signal processing, 2019)
•This paper explores the adaptive fault-tolerant control of quadrotor helicopters.•Actuator faults, parametric uncertainties, and disturbances can be all compensated.•With the aid of proposed adaptive schemes, control chattering problem is avoided. This paper presents a disturbance observer-based adaptive sliding mode control (SMC) strategy for a quadrotor helicopter subject to multiple actuator faults, parametric uncertainties, and external disturbances. Unlike most of the existing control strategies for quadrotor helicopters, actuator faults, parametric uncertainties, and external disturbances can be simultaneously compensated within the proposed control scheme. Firstly, by employing the adaptive control parameters in both continuous and discontinuous control parts, the proposed control strategy can generate appropriate control signals to accommodate actuator faults and parametric uncertainties without merely relying on the robust discontinuous control strategy of SMC. Then, a nonlinear disturbance observer is designed and integrated to attenuate external disturbances while keeping the small value of the discontinuous control gain of SMC. In addition, the stability analysis of the proposed control strategy is given, showing that the presented controller can ensure system tracking performance and make the tracking errors arbitrarily small under the concerned situation. The effectiveness of the proposed control strategy is demonstrated through comparative numerical simulations and experimental tests of a quadrotor helicopter under different faulty and uncertain scenarios.